Arugang salu-salo, para kay lola't lolo intergenerational solidarity in elderly grandparent care as discussed within Filipino families from selected cities of Metro Manila - Osido, Floren Camille B. 1993-; Osido, Floren Camille B.; Pantaleon, Ma. Gabrielle T.; Cubelo, Julienne Thesa Baldo; University of the Philippines Diliman. College of Mass Communication (2015)
"This study looks at how elderly grandparent care is discussed and carried out whithin multigenerational families from selected cities of Metro manila, namely Quezon City, Muntinlupa City, and Pasig City. The elderly have been known to be domestic concern, given our culture of filial piety, wherein younger generations have the responsibility of taking care of the elderly. Another factor of the insufficiency of government provisions and benefits for the elederly. Using Bangston's intergenerational solidarity paradigm, we wanted to discover the positive family dynamics behind elderly grandparent care. Using the focus interview method, we looked at the family's daily routine, bonding activities, relationship closeness, perceptions of elderly care and what care they provided, and the degree of participation of the elderly grandparent in carrying out this said care. Based on our findings, elderly care is a complex concept that goes beyond the process as it involves several components. Planning for care was also done spontaneously and only when needed, and we found that there is interplay between the concern of the family carrying out the acre and the elderly still wanting to be independent of their family members' care while they are still capable of doing things on their own. This relationship illustrates a paradox that is meant to be balanced and managed between both concerned groups."
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Older people -- Care; Older people -- Home care; Families -- Philippines; Family relationships -- Philippines